Competitiveness strategy in developing countries - Wignaraja, Ganeshan, 1962- (Routledge studies in development economics, 2003)
Globalization and structural adjustment offer many opportunities for export orientated industrialization in developing economies. As a group, competitiveness in the developing countries has improved, but, while East Asian economies have had rapid export growth and technological upgrades, South Asian and African economies have lagged behind. Old structures, institutions, behavioural patterns and public policies are ill-adapted to deal with the challenges posed by technological change and economic liberalization. Consequently there is an urgent need for change in government and private sector at.